Long‐term outcomes following intravascular lithotripsy (IVL) for calcified coronary lesions: A Real‐World Multicenter European Study. Issue 2 (16th December 2022) - Basavarajaiah, Sandeep; Ielasi, Alfonso; Raja, Waseem; Naneishvili, Tamara; Testa, Luca; Popolo Rubbio, Antonio; Mastrangelo, Angelo; Bartorelli, Antonio L.; Bhatia, Gurbir; Choudhury, Anirban; Sundara‐Raman, Ajay; Buono, Andrea; et al.
Abstract: Objectives: To explore the long‐term clinical outcomes following intravascular lithotripsy (IVL) in calcified coronary lesions from a real‐world population. Background: IVL is a relatively new but promising modality for treating coronary calcified lesions, but there is a dearth of long‐term outcome data from real‐world patients. Methods: This was a multicenter, observational study in which we enrolled all patients treated with IVL from November 2018 to February 2021 from eight centers in Europe and the United Kingdom. Procedural success, complications, and clinical outcomes (cardiac death, target vessel myocardial infarction [TVMI], target lesion revascularization [TLR], and MACE [major adverse cardiac events, the composite of cardiac death, TVMI, and TLR]) were assessed. Results: In total, 273 patients with a mean age of 72 ± 9.1 years were treated with IVL. Major comorbidities included diabetes mellitus ( n  = 110, 40%) and chronic kidney disease ( n  = 45, 16%). Acute coronary syndrome accounted for 48% ( n  = 132) of patients, while 52% ( n  = 141) had stable angina. De novo lesions and in‐stent restenosis accounted for 79% and 21% of cases, respectively. Intravascular imaging was used in 33% ( n  = 90) of patients. An upfront IVL strategy was adopted in 34% ( n  = 92), while the rest were bailout procedures. Adjuvant rotational atherectomy ("RotaTripsy") was required in 11% ( n  = 31) of cases. The procedural success was 99%. During a median follow‐up of 687 days (interquartile range: 549–787), cardiac death occurred in 5% ( n  = 14), TVMI in 3% ( n  = 8), TLR in 6% ( n  = 16), and MACE rate was 11% ( n  = 30). Conclusion: This is the largest multicenter registry with a long‐term follow‐up showing the remarkably high procedural success of IVL use in calcified coronary lesions with low rates of hard endpoints and MACE.